Magnetic resonance angiography in diagnostic long-term follow-up of primary patency of the MOTIV drug-eluting bioresorbable vascular scaffold in the region below the knee: 5 years of experience - Christian Nasel; Mario Kirschner; Karoline Rizzi; Nicola Schweinhammer; Ewald Moser (PLoS ONE, 2025)
Purpose Treatment of peripheral artery disease (PAD) in the region below the knee (BTK) is dissatisfying as failure of treated target lesions (TLF) is frequent and diagnostic imaging is often challenging. In the BTK-region metallic drug-eluting stents (mDES) yielded best results concerning primary patency (PP), but also annihilate signal in magnetic resonance angiography (MR-A). A recently introduced non-metallic drug eluting bioresorbable Tyrocore® vascular scaffold (deBVS), that offers an option for re-treatment of lesions due to its full degradation within 3–4 years after placement, was investigated with respect to its compatibility with MR-A to unimpededly depict previously treated target lesions. Methods Patency of the deBVS in the BTK-region was assessed retrospectively using contrast enhanced MR-A of the lower limbs in patients with PAD of Lafontaine-grades II-IV (n = 19). Clinically driven MR-A censoring was triggered by an assumed target lesion failure (CD-TLF), which served to compute the probability of PP during the observation period of 5 years. Compatibility of this particular deBVS with MRI was additionally proven via in-vitro experiments. Results The scaffold was found to be fully compatible with MRI. The normalised intra-luminal signal measured in MR-A increased significantly after successful deBVS-placement. The retrospective 5-years PP-probability was 0.87 (CI95%: [0.71,1.0]) with 2 stent-occlusions observed after 90 days. No major adverse events occurred. Conclusion Assessment of PAD in the BTK-region after placement of the Tyrocore®-deBVS using MRA is feasible. The promising high PP-probability after 5-years and the persistent full interpretability of treated target lesions by MR-A after stent-placement encourage further prospective assessment of this deBVS in treatment of PAD in the BTK-region.